Development of Electronic Student Worksheet Based on Problem-Based Learning With A Socioscientific Issue Approach on the Digestive System Material - Adha Febrianti; Afreni Hamidah; Danial Mursyd (Al Jahiz, 2026)
This study aims to develop e-student worksheet based on Problem Based Learning with Socioscientific Issue approach on digestive system material for grade XI phase F students. The method used is Research and Development (R&D) with the ASSURE development model. e-student worksheet products are designed to be accessible electronically through various devices and integrate interactive elements such as videos, minigames, and real-world problem-based materials related to social and scientific aspects. The development results state that the e-student worksheet learning media has been developed using the ASSURE model with 6 stages, namely analyze learner; state standard and objectives; select methods, media and materials; utilize technology, media and materials; require learner participation; and evaluation & revision and is declared very suitable for use with a material validation value of 95% and media validation of 91.66%. The results of biology teachers' perceptions with a value of 95.45%, which means it can be accepted to be used as a source of learning media. The results of small group trials obtained student responses in the very good category, namely 82.98% and large group trials in the very decent category, namely 88.31%, so the product is suitable for use. This study produced a product that can overcome students' difficulties in understanding learning materials, especially digestive system materials found in the validation process of material experts, media experts, trials with biology teachers, students, and the results of student learning improvements from pretest-posttest.